Comparison fermentation kinetics (in vitro) of grass and shrub legume leaves: The pattern of VFA concentration, estimated CH4 and microbial biomass production - Widiawati, Y; Thalib, A (Indonesian Animal Sciences Society, 2007)
In the process of fermentation, rumen microbes normally convert major fractions of carbohydrates and proteins in a feed to useful end-products (i.e. VFA, microbial protein and B-vitamins) and some waste products (i.e. CH4 and CO2). The pattern of these end-products depend largely on the fraction contained in the feed eaten by the animal. Two types of feeds, namely grass and shrub legume, leucaena have different fraction proportions. Grass contains more fibre but less protein compared to shrub legumes. Thus in the rumen they might be fermented to produce different pattern of end products. The experiment was conducted in order to examine the pattern of VFA, CH4 and microbial protein products of the two types of feeds when fermented in the rumen. In vitro method was used to determine the pattern of these end products. Results showed that the grass produced more total VFA/mg organic matter degraded (0.0229 mM/mg vs 0.0075 mM/mg) and CH4 gasÂ (0.20 mole/mg Â vs 0.09 mole/mg) but less propionate in partial and less microbial protein (2646 g vs 2656 g ) compared to the legume. Approximately 32% less CH4 (per mg OM degraded) would be produced from leucaena compared to that produced from grass, which mean that there will be less energy loss as CH4 thus more energy for animal production. Key Words: Grass, Shrub Legume, Volatile Fatty Acids, CH4, Microbial Protein